THE PSYCHOLOGICAL BASIS OF STUDENTS’ SELF-REALIZATION AT THE INTEGRATED EDUCATIONAL ENVIRONMENT - Danyliuk, Ivan; Kuprieieva, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In the space of modern Ukrainian higher education, the tasks of vocational training development and improvement, integration and creating conditions for disabled students’ creative self-realization become really important. In order to create the structure of adapted environment at universities and to promote personal and professional development of all participants at the integrated educational environment, a comprehensive psychological study of the psychological foundations of students' personal self-realization should be done. The research objective: to study psychological characteristics of students’ self-realization studied at integrated groups with investigation of disabled students’ self-attitudes and their correlations with self-actualization, meaningful life orientations and psychological hardiness. Research methods: the test-questionnaire of self-attitudes (S. Pantileev, V. Stolin); Shostrom's Personal Orientation Inventory in adaptation N. Kalin, A.Lazukin; the Test of Meaningful Life Orientation of D.L.Leontev; S.Maddi's Hardiness Scale in adaptation of D.Leontiev, Ye.I. Raskasova; the methods of statistical analysis for empirical data: comparative analysis of average indicators, correlation analysis. The performed empirical study revealed such psychological characteristics of disabled students’ self-attitudes as unrealistic ideas about themselves, their abilities and skills, a tendency to self-blame, low level of self-understanding, which can become obstacles to their effective self-realization. The success of students' self-realization in the integrated educational environment of universities is provided by their internal resources: positive self-attitude, awareness of goals, meanings in life, strength and stability of Self, cooperation with other people, society as a whole.